Sosialisasi Kegiatan Ekonomi Perikanan Masyarakat sebagai Upaya Pencegahan Ilegal Fishing serta Dampaknya bagi Ekosistem Perairan di Kelurahan Kameloh Baru Kecamatan Sebangau Kota Palangka Raya - Bagus Prasetyo; Alyaziza Aisya; Monica Monica (MANGENTE: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
Kameloh Baru Village is an area in Sebangau District, Palangka Raya City, where the majority of the population works as fishermen. The community's economic activities are highly dependent on the freshwater fishery ecosystem of the Kahayan River. However, there are some people who do fishing with methods and tools that are prohibited by law (illegal fishing). Based on these facts, this service is carried out with the aim of creating good economic activities without damaging the aquatic ecosystem and fish farming in the area. The regulation used is Law Number 31 of 2009 concerning Fisheries in Article 84 with a threat of 6 years imprisonment and a maximum fine of Rp. 1.2 billion. The Department of Fisheries and Villages in collaboration with KKN Students of the Palangka Raya State Islamic Institute carried out activities to support the fishery ecosystem by restocking, and socializing education in the field of fishery economy as an effort to prevent illegal fishing. The activity was successful and received a positive response from the head of the RT and the whole community who work as fishermen, it is hoped that it can change the bad habits of the people who still catch fish in a way that is prohibited by law.